Cosmic apprentice : dispatches from the edges of science - Sagan, Dorion, 1959- (University of Minnesota Press, 2013)
Refreshingly nonconformist and polemically incisive, this book challenges readers to reject both dogma and cliché and instead recover the intellectual adventurousness that should - and can once again - animate both science and philosophy. Informed by a countercultural sensibility, a deep engagement with speculative thought, and a hardheaded scientific skepticism, it advances controversial positions on such seemingly sacrosanct subjects as evolution and entropy.